2008
DOI: 10.1007/s10911-008-9090-8
|View full text |Cite
|
Sign up to set email alerts
|

MMTV Infectious Cycle and the Contribution of Virus-encoded Proteins to Transformation of Mammary Tissue

Abstract: Mouse mammary tumor virus has served as a major model for the study of breast cancer since its discovery 1920's as a milk-transmitted agent. Much is known about in vivo infection by this virus, which initially occurs in lymphocytes that then carry virus to mammary tissue. In addition to the virion proteins, MMTV encodes a number of accessory proteins that facilitate high level in vivo infection. High level infection of lymphoid and mammary epithelial cells ensures efficient passage of virus to the next generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 79 publications
(85 reference statements)
1
28
0
1
Order By: Relevance
“…They showed that ectopic expression of MMTV Env in normal mammary epithelial cells resulted in phenotypic transformation, and an activation motif in this protein (the Immunoreceptor Tyrosine-based Activation Motif -ITAM) was critical to that activity. Although subsequent studies (using Env expression in transgenic mice) indicated that ITAM is not sufficient for cellular transformation, Env signaling, nevertheless, takes part in MMTVmediated transformation, as mutation of the ITAM reduces virus-induced mammary tumorigenesis (48,49). Taken together, our findings and those of Ross's group are consistent with a role for the Env protein and its signal peptide in regulating the tumorigenic potential of MMTV-infected cells.…”
Section: Discussionsupporting
confidence: 83%
“…They showed that ectopic expression of MMTV Env in normal mammary epithelial cells resulted in phenotypic transformation, and an activation motif in this protein (the Immunoreceptor Tyrosine-based Activation Motif -ITAM) was critical to that activity. Although subsequent studies (using Env expression in transgenic mice) indicated that ITAM is not sufficient for cellular transformation, Env signaling, nevertheless, takes part in MMTVmediated transformation, as mutation of the ITAM reduces virus-induced mammary tumorigenesis (48,49). Taken together, our findings and those of Ross's group are consistent with a role for the Env protein and its signal peptide in regulating the tumorigenic potential of MMTV-infected cells.…”
Section: Discussionsupporting
confidence: 83%
“…Resistance is due in most cases to lack of infection or virus spread within the lymphoid compartment. The MMTV genome encodes a superantigen (Sag) protein which is presented by major histocompatibility complex (MHC) class II molecules on antigenpresenting cells, such as DCs, to T cells, thereby inducing their activation (34). Activated T cells in turn activate bystander antigen-presenting cells, ultimately resulting in virus amplification in the lymphoid compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The HERV-K (HML-2) proviruses (4-9), so-named for their use of a Lys tRNA primer and similarity to the mouse mammary tumor virus (human MMTV like) (10), represent an exception to the antiquity of most HERVs. HML-2 has contributed to at least 120 human-specific insertions, and population-based surveys indicate as many as 15 unfixed sites, including 11 loci with more or less full-length proviruses (5,6,8,9).…”
mentioning
confidence: 99%